Foreign Direct Investment, Exports, and Domestic Output in Pakistan (The Pakistan Development Review, 2003)
The impact of the policy reform on economic performance has been one of the stifling issues in development economics in the recent years. Since the middle 1970s, there has been considerable progress in the trade reform in the most developing countries, turning from an import substitution strategy to export-oriented approach. Pakistan also follows export-oriented policies. Pakistan’s trade pattern and trade policy have been moving towards fewer and fewer controls, tariffs rates have come tumbling down. Export-led-growth hypothesis (ELG) suggests that due to positive correlation between export and growth, therefore, export-oriented policies contribute to economic growth. Thus, international trade and development theory suggests that export growth contributes positively to economic growth. On the basis of this framework, most empirical work on the effects of export promoting strategy followed in developing countries evaluated openness with trade. Empirical research about the effect of this liberalisation process has treated export as principal channel for growth. The relationship with exports and growth, grounded in endogenous growth theory, has been tested for Pakistan [Khan (1995); Ahmad, Butt, and Alam (2000) and Akbar (2000)].